Tinjauan Yuridis Peninjauan Kembali Lebih Dari Satu Kali Perkara Tata Usaha Negara: Putusan Mahkamah Agung Nomor 91 Pk/Tun/2017 Antara Pt. Semen Indonesia Persero Tbk Melawan Yayasan Wahana Lingkungan Hidup Indonesia - Muh. Aunur Rafiq; Irfan Khairul Umam (JOURNAL of LEGAL RESEARCH, 2021)
Multiple reviews in the sphere of TUN provide various legal difficulties, including the absence of a clear legal instrument governing the verification of novum that has not been materially demonstrated to be viable. Additionally, there has been a clash between legal certainty and justice in conducting the Judicial Review on multiple occasions. The research is normative-juridical in nature. The research is based on a legal examination of statutes and regulations, as well as jurisprudence or judge's decisions pertaining to the review of many State Administrative cases, which can then be incorporated into a new legal rule to facilitate legal thinking. The objective of this study is to explain the review process many times in the sphere of State Administration and to examine the legal concerns of judges while considering PK TUN cases multiple times. Article 132 of the Administrative Court Law establishes the legal basis for PK in the sphere of TUN, which is further defined in SEMA Number 10 of 2009. This study demonstrates the panel of judges' inconsistency in judging cases. At the 2nd PK stage, the applicant established in his novum that the novum given by the First PK Petitioner was a forgery, but the 2nd PK judge rejected the proof, stating that the Judicial Power Act specified that the maximal PK effort may be made only once.